2022
DOI: 10.1186/s12864-022-08412-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into lineage-specific evolution of the oleosin family in Euphorbiaceae

Abstract: Background Lipid droplets (LDs) present in land plants serve as an essential energy and carbon reserve for seed germination and seedling development. Oleosins, the most abundant structural proteins of LDs, comprise a small family involved in LD formation, stabilization and degradation. Despite their importance, our knowledge on oleosins is still poor in Euphorbiaceae, a large plant family that contains several important oil-bearing species. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 76 publications
(89 reference statements)
1
11
0
Order By: Relevance
“…Transcripts encoding 2S albumin-like (Unigene0003223, Unigene0049069, Unigene0046600, Unigene0011183, and Unigene0048736), legumin-like (Unigene0048787, Unigene0010858, and Unigene0010856) and vicilin-like proteins (Unigene0049803 and Unigene0044374) were also abundant; these proteins are specifically synthesized during seed maturation. Other abundant transcripts of the Oleosin genes (Unigene0044871, Unigene0028565, and Unigene0050906) are highly abundant in land plants and could positively regulate total seed oil accumulation [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transcripts encoding 2S albumin-like (Unigene0003223, Unigene0049069, Unigene0046600, Unigene0011183, and Unigene0048736), legumin-like (Unigene0048787, Unigene0010858, and Unigene0010856) and vicilin-like proteins (Unigene0049803 and Unigene0044374) were also abundant; these proteins are specifically synthesized during seed maturation. Other abundant transcripts of the Oleosin genes (Unigene0044871, Unigene0028565, and Unigene0050906) are highly abundant in land plants and could positively regulate total seed oil accumulation [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we used Brassicales, an economically important order of flowering plants that harbors the lineage-specific T clade [ 3 , 8 , 17 ], as an example to address evolution patterns of the oleosin gene family. In addition to 34 members reported in Arabidopsis, cassava, and poplar ([ 12 ], this study), a number of 64 oleosin family genes were identified from ten species representing eight plant families, i.e., Amborellaceae ( A. trichopoda ), Lauraceae (avocado), Ranunculaceae ( A. coerulea ), Caricaceae (papaya), Moringaceae (horseradish), Akaniaceae ( B. sinensis ), Capparaceae (caperbush), and Cleomaceae ( C. violacea , acaya, and spider flower), while gene numbers of the family vary from three to ten. Interestingly, the family amounts are usually higher in species that experienced recent WGDs.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, compared with five members present in both A. trichopoda and A. coerulea , one more was identified in papaya, horseradish, and C. violacea . By contrast, more than seven members were identified in B. sinensis , acaya, and spider flower, which are comparative to eight and nine reported in cassava and poplar, respectively [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations